Emerging immunological drugs for chronic lymphocytic leukemia. (September 2015) - Robak, Pawel; Smolewski, Piotr; Robak, Tadeusz
<x xml:space="preserve">Abstract</x> Introduction: Over the last few years, several new immunological drugs, particularly monoclonal antibodies (mAbs), immunomodulatory drugs and B-cell receptor (BCR) pathway inhibitors have been developed and investigated in chronic lymphocytic leukemia (CLL). This article summarizes recent discoveries regarding their mechanism of action, pharmacological properties, clinical activity and toxicity, as well as the emerging role of these agents in CLL. Areas covered: A literature review of mAbs, BCR pathway inhibitors and immunomodulating drugs was conducted of the MEDLINE database via PubMed for articles in English. Publications from 2000 through February 2015 were scrutinized. The search terms used were alemtuzumab, BI 836826, duvelisib ibrutinib, idelalisib, lenalidomide, monoclonal antibodies, MEDI-551, MOR208, obinutuzumab, ocaratuzumab, ofatumumab, ONO-4059, otlertuzumab, spebrutinib, veltuzumab and XmAb5574 in conjunction with CLL. Conference proceedings from the previous 5 years of the American Society of Hematology, European Hematology Association, American Society of Clinical Oncology, and ACR/ARHP Annual Scientific Meetings were searched manually. Additional relevant publications were obtained by reviewing the references from the chosen articles. Expert opinion: The use of mAbs, BCR inhibitors and immunomodulating drugs is a promising new strategy for chemotherapy-free treatment of CLL. However, definitive data from ongoing and future clinical trials will aid in better defining the status of immunological drugs in the treatment of this disease.